Protective effect of androgens against inflammation induced cartilage degradation in male rodents. Issue 4 (April 1993) - Da Silva, J A; Larbre, J P; Spector, T D; Perry, L A; Scott, D L; Willoughby, D A
Abstract : OBJECTIVES--Rheumatoid arthritis (RA) is a disease which predominantly affects women. Interestingly, low serum androgen levels and clinical improvement with androgen replacement have been reported in male patients. The aetiopathogenic role of sex hormones in arthritis and their potential long term effects on joint destruction and disability remains unclear, however. This study was designed to investigate the potential influence of sex hormones on inflammation induced cartilage degradation in male rodents. METHODS--An in vivo model of cotton wrapped cartilage implants was used to assess the effects of androgen, oestradiol, and progesterone on inflammation induced cartilage degradation, and in vitro techniques were used to investigate the direct actions on cartilage metabolism and cytokine production in male animals. RESULTS--Orchidectomy resulted in accelerated cartilage damage which was reversed by replacement of physiological levels of androgens. Granulomatous tissue from castrated male rodents produced higher amounts of interleukin 1. Sex hormones reduced spontaneous proteoglycan loss in vitro but did not interfere with the effects of interleukin 1 on cultured cartilage. CONCLUSIONS--Androgens appear to protect cartilage from inflammation induced breakdown in male animals. These results support a pathogenic role for hypoandrogenism in rheumatoid arthritis and suggest that long term androgen replacement may help prevent joint damage and disability.